Reproduksi Kultural Komunitas Sastra “Pawon Sastra” Di Surakarta, Jawa Tengah - Dwi Susanto; Susanto Susanto; Bagus Kurniawan (JURNAL SOSIAL HUMANIORA (JSH), 2019)
Pawon Sastra's literary community in Surakarta has conducted cultural and social practices. It brings impacts and responses from society. The main topic of this research is social and cultural practices carried out by the Pawon Sastra community as a form of reciprocal relations with the structure surrounding it, which similar to the interaction between the structure and agent. We used a sociological point of view, especially agents, construction, and actions. The problems of this research are (1) how the agent responds to the social structure and (2) what kind of cultural practices are manifested by the agent, and (3) what impact arises as to the result of the cultural practices by the agent. The research was carried out using the qualitative method. The data used were the activities of the literary community, the results of their work, and the subjects involved in the city. The results of this study indicated that social practices were carried out in various ways such as publishing, the reinterpretation of traditions, or publications as a form of interaction among similar communities. Moreover, the impact on social structures was the increase in the formation of the same populations and the emergence of new individuals who follow the footsteps of Pawon Sastra. This is also enhanced by various interactions occurring in the social environment of the newly established community.